USING SCANNING AND SKIMMING STRATEGY TO IMPROVE THE STUDENTS’ READING COMPREHENSION - Sari, Shinta Maya Sari (Faculty of Teaching and Education, University of August 17, 1945, Banyuwangi, 2023)
The main purpose of this research is to improve students’ reading comprehension by implementing scanning and skimming strategy. Classroom action research (CAR) was chosen to solve the problems in learning process. There are four stages in implementing CAR: planning; implementing; observing; reflecting. Data of the were collected from students’ active involvement and students’ reading score. 31 students voluntarily participated in the study. The data of the study were collected from observation checklist and reading test. The quantitative data from observation checklist and reading test were analyzed by descriptive comparative statistical techniques that is comparing the calculated result from descriptive statistic, example the mean, median, frequency, or percentage in one cycle with the next cycle. The students’ mean score in reading test in cycle 1 was 80.32. Moreover, observation sheet showed that 80.65% of 31 students were active in the first meeting listening class. In cycle 2, the mean score was 81.45 and there were 28 students or 90.32% out of 31 students could achieve the target score of the product evaluation. Furthermore, observation sheet showed that 87.09% of 31 students were active in the first meeting reading class. Then, 93.55% of 31 students were active in the second meeting. The present study concludes that scanning and skimming strategy were effective to help students learn reading skill. The strategy can also foster students’ engagement.